A Study of Race Pacing in the Running Leg of the Japan University Triathlon Championship - Inai, Yuto; Aoyagi, Atsushi; Ishikura, Keisuke; Namatame, Hayate; Nabekura, Yoshiharu; Akama, Takao (Frontiers in Sports and Active Living, 2022)
Choosing an appropriate pacing strategy is important for good triathlon performance. In the Japan Student Triathlon Championship held in 2020, the men's category was divided into two groups, which was a different racing style from the previous races that all athletes start at the same time. It is highly likely that the performance level will vary as grouping was performed according to the competence of each player. The aim of this study was to understand the relationship of the total time and time of each leg between the superior performance group and the inferior performance group, as well as the difference in pacing during running in participants of the 2020 Japan University Triathlon Championship Watarase Competition, which was held under unconventional conditions. We analyzed 153 male athletes (Group A: 77; Group B: 76) who completed the race. The total race time, leg time, and average speed in each leg and its variation coefficient were evaluated based on the official results of the competition and footage recorded during the race. The results showed that the total time and leg time for each leg were significantly shorter in Group A compared to those in Group B (p < 0.05). In both groups, the Lap 4 run was significantly slower than those of Laps 1–3 (p < 0.05), while there was no significant difference in the running speed to average speed ratio across all laps between the groups (p < 0.05). Thus, there was a difference in running speed between the groups, but no significant difference in pacing. The results of this study serve as basic data for examining superior pacing strategies, although further studies on a wide range of competition levels are necessary.